Kinetic and thermodynamic evaluation of effective combined promoters for CO2 hydrate formation - Abu Hassan, MH; Sher, F; Zarren, G; Suleiman, N; Tahir, AA; Snape, CE (Elsevier Sci Ltd, 2024)
Indexed by WOS/ Scopus